Effects of oxygen therapy on wall‐motion score index in patients with ST elevation myocardial infarction—the randomized SOCCER trial - Khoshnood, Ardavan; Akbarzadeh, Mahin; Roijer, Anders; Meurling, Carl; Carlsson, Marcus; Bhiladvala, Pallonji; Höglund, Peter; Sparv, David; Todorova, Lizbet; Mokhtari, Arash; Erlinge, David; Ekelund, Ulf (Echocardiography (Mount Kisco, N.Y.), 2017)
Background Although oxygen (O2) is routinely used in patients with acute myocardial infarction (AMI), it may have negative effects. In this substudy of the SOCCER trial, we aimed to evaluate the effects of O2‐treatment on myocardial function in patients with ST elevation myocardial infarction (STEMI). Methods Normoxic (≥94%) STEMI patients were randomized in the ambulance to either supplemental O2 or room air until the end of the percutaneous coronary intervention (PCI). The patients underwent echocardiography on day 2–3 after the PCI and once again after 6 months. The study endpoints were wall‐motion score index (WMSI) and left ventricular ejection fraction (LVEF). Results Forty‐six patients in the O2 group and 41 in the air group were included in the analysis. The index echocardiography showed no significant differences between the groups in WMSI (1.32±0.27 for O2 group vs 1.28±0.28 for air group) or LVEF (47.0±8.5% vs 49.2±8.1%). Nor were there differences at 6 months in WMSI (1.16±0.25 vs 1.14±0.24) or LVEF (53.5±5.8% vs 53.5±6.9%). Conclusion The present findings indicate no harm or benefit of supplemental O2 on myocardial function in STEMI patients. Our results support that it is safe to withhold supplemental O2 in normoxic STEMI patients.